Social media use and depressive symptoms among United States adolescents - Kreski, Noah (J Adolesc Health, 2020)
PURPOSE: Depression is increasingly common among US adolescents; the extent to which social media exposure contributes to this increase remains controversial. METHODS: We used Monitoring the Future data from 8(th) and 10(th) grade students (n=74,472), 2009–2017, to assess the relationship between daily social media use and depressive symptoms. Self-reported depressive symptom score (range: 4–20) was assessed continuously using a log-transformed outcome and at varying cutscores with logistic regression analyses. First, these outcomes were examined overall, comparing adolescents using social media daily to adolescents who were not. We then estimated predicted depressive symptom scores using 26 predictors in order to establish underlying depression risk. We partitioned students into depression risk quintiles to control for confounding due to underlying depression risk and examine heterogeneity in the association between social media use and depressive symptoms. Sensitivity analyses were used to test the robustness of results with different configurations of the predicted score model, and overall associations were examined in two-year groups to identify differences in effects. RESULTS: For girls, in adjusted risk-stratified analysis, daily social media use was not associated with high (vs low) depressive symptoms. For boys, results were inconsistent, suggesting a protective effect of daily social media use at some cutscores. Results were consistent across sensitivity analyses, and any potential harmful effects appear to be limited to 2009–2010, limiting the evidence supporting social media as a current risk factor for depressive symptoms. CONCLUSIONS: Among US adolescents, daily social media use is not a strong or consistent risk factor for depressive symptoms.